Blogging together: An examination of group blogs - Hearst, Marti A.; Dumais, Susan (ICWSM 2009, 2009)
This paper presents the ﬁrst examination of the growing phenomenon of multi-author, or group blogs. Using a large collection of blog posts gathered over an eight month period, we conducted some quantitative assessments. Multi-author blogs were found to differ signiﬁcantly from single-and-two author blogs on several quality metrics, including having longer posts on average and being ranked higher according to an inlink metric. Visualization of patterns of posting revealed that individual authors often dominate the posts in multi-author blogs, and that in some cases tags are shared, but usually not extensively.